Site-specific mutagenesis of histidine residues in the lac permease of Escherichia coli. - Padan, E (1985)
The lacY gene of Escherichia coli, which encodes the lac permease, has been modified by oligonucleotide-directed, site-specific mutagenesis such that each of the four histidine residues in the molecule is replaced with an arginine residue. Replacement of histidine-35 and histidine-39 with arginine has no apparent effect on permease activity. In contrast, replacement of either histidine-205 or histidine-322 by arginine causes a dramatic loss of transport activity, although the cells contain a normal complement of permease molecules, as determined by immunoadsorption assays. Interestingly, although substitution of histidine-205 or histidine-322 by arginine results in the loss of ability to catalyze active lactose transport, permease molecules with arginine at residue 322 appear to facilitate downhill lactose movements at high concentrations of the disaccharide. The results provide strong support for the contention that histidine residues in the lac permease play an important role in the coupling between lactose and proton translocation.